Three-Photon Pulse Interference in a Tritter: A Novel Approach for a Three-Party Quantum Key Distribution Protocol - Suryadi; Precious O. Amadi; Norshamsuri Ali (Physics)
This study presents a theoretical investigation into the interference properties of three photons in a six-port optical beam splitter, commonly referred to as a tritter. We examine various configurations of the relative phase differences among the input photons. Our findings reveal that fully constructive interference periodically occurs at a single output port for specific constant phase differences, while fully destructive interference simultaneously manifests at the remaining two output ports. These distinctive interference patterns arise across a wide range of specific phase difference combinations among the input photons. We suggest that these unique interference characteristics provide new insights into the potential implementation of a three-party quantum key distribution protocol. Such three-photon interference phenomena are crucial for facilitating symmetric secure key distribution among three parties.